Generation of mice carrying a knockout‐first and conditional‐ready allele of transforming growth factor beta2 gene. Issue 9 (9th June 2014) - Ishtiaq Ahmed, A. S.; Bose, Gracelyn C.; Huang, Li; Azhar, Mohamad
Summary Transforming growth factor beta2 (TGFβ2) is a multifunctional protein which is expressed in several embryonic and adult organs. TGFB2 mutations can cause Loeys Dietz syndrome, and its dysregulation is involved in cardiovascular, skeletal, ocular, and neuromuscular diseases, osteoarthritis, tissue fibrosis, and various forms of cancer. TGFβ2 is involved in cell growth, apoptosis, cell migration, cell differentiation, cell‐matrix remodeling, epithelial‐mesenchymal transition, and wound healing in a highly context‐dependent and tissue‐specific manner. Tgfb2−/− mice die perinatally from congenital heart disease, precluding functional studies in adults. Here, we have generated mice harboring Tgfb2βgeo (knockout‐first lacZ‐tagged insertion) gene‐trap allele and Tgfb2flox conditional allele. Tgfb2βgeo/βgeo or Tgfb2βgeo/‐ mice died at perinatal stage from the same congenital heart defects as Tgfb2−/− mice. β‐galactosidase staining successfully detected Tgfb2 expression in the heterozygous Tgfb2βgeo fetal tissue sections. Tgfb2flox mice were produced by crossing the Tgfb2+/βgeo mice with the FLPeR mice. Tgfb2flox/− mice were viable. Tgfb2 conditional knockout (Tgfb2cko/−) fetuses were generated by crossing of Tgfb2flox/− mice with Tgfb2+/−; EIIaCre mice. Systemic Tgfb2cko/− embryos developed cardiac defects which resembled the Tgfb2βgeo/βgeo, Tgfb2βgeo/−, and Tgfb2−/− fetuses. In conclusion, Tgfb2βgeo and Tgfb2flox mice are novel mouse strains which will be useful for investigating the tissue specific expression and function of TGFβ2 in embryonic development, adult organs, and disease pathogenesis and cancer. genesis 52:817–826, 2014. © 2014 Wiley Periodicals, Inc.